Economics Valuation of Mangrove Forest in Supporting the Blue Economy and the Maqasid Al Sharia: A Case Study of Guraping Mangrove Forest, Sofifi, North Maluku - Wongsokarto, Misdiarso; Setiawan, Achma Hendra (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2024)
This research aims to evaluate the economic value of the Guraping mangrove forest in Sofifi, Indonesia, and its alignment with blue economy principles and Maqaṣid al-Sharia objectives. This research uses a mixed-methods approach, combining quantitative and qualitative methods. Data were collected through surveys using questionnaires from 100 tourists, interviews with key informants, observations, and literature reviews. The results of the valuation economy support the concept of the blue economy and Maqaṣid al-Sharia. Guraping's mangrove forests positively contribute to the blue economy with direct and indirect use values. Besides, this economic valuation is also relevant in achieving Maqaṣid al-Sharia goals that emphasize the conservation of nature and sustainable socio-economic well-being. Penelitian ini bertujuan untuk mengevaluasi nilai ekonomi hutan mangrove Guraping di Sofifi, Indonesia, serta kesesuaiannya dengan prinsip ekonomi biru dan tujuan Maqaṣid al-Sharia. Penelitian ini menggunakan pendekatan campuran, yang menggabungkan metode kuantitatif dan kualitatif. Data dikumpulkan melalui survei dengan kuesioner kepada 100 wisatawan, wawancara dengan informan kunci, observasi, dan tinjauan pustaka. Hasil penilaian ekonomi mendukung konsep ekonomi biru dan Maqaṣid al-Sharia. Hutan mangrove Guraping memberikan kontribusi positif terhadap ekonomi biru melalui nilai pemanfaatan langsung dan tidak langsung. Selain itu, penilaian ekonomi ini juga relevan untuk mencapai tujuan Maqaṣid al-Sharia yang menekankan konservasi alam dan kesejahteraan sosial-ekonomi yang berkelanjutan.